THE EFFECT OF ARGENTUM AND CADMIUM TOWARDS ASTAXANTHIN CONTENT IN GREEN ALGAE, HAEMATOCOCCUS PLUVIALIS - Cheng, Wan Hee; Wong, Ling Shing; Hong, Yee Zhen; Tan, Yong Man; Ahmad, Zaharin Aris (Global Science Publications, 2018)
- Haematococcus pluvialis is a kind of microalgae with high potential in the production of astaxanthin- a secondary carotenoid with high commercial values. However, the mass production of astaxanthin is still not possible due to the low yield of astaxanthin obtained from this alga. The present study is aimed to determine the potential of Ag and Cd to enhance the production of astaxanthin in H. pluvialis at optimal pH and salinity. The alga was cultured in a series of different concentrations of Ag and Cd nanoparticles for 30 days, with pH 7 and salinity of 0.25%. The cell density and astaxanthin content were determined at day 15 and day 30. Highest accumulation of astaxanthin in the algae were found in the exposed concentration 10 ppm for both Ag(2.83 ± 0.70 mg/L) and Cd (4.98 ± 0.09 mg/L) nanoparticles at day 30. The amount of cell density and astaxanthin content in the algae decreased with the exposure of higher concentration of metal nanoparticles. Argentum nanoparticles were more toxic to the algae as both cell density and astaxanthin production for day 15 and 30 were lower than control. It can be concluded that Cd is a good inducer of astaxanthin production in H. pluvialis.